Global food security concerns and agricultural trade: Building a responsible and effective relationship - Campos Azofeifa, Adriana; Elverdin, Pablo (International Food Policy Research Institute, 2024)
Since the Agreement on Agriculture came into effect trade in food has quintupled. The rules agreed under the framework of the World Trade Organization (WTO) allowed developing countries to join external markets and increase their participation to the point that they now account for two thirds of the overall flow of agricultural trade.